TEKANAN SOSIAL BUDAYA DAN PERKAWINAN ANAK DALAM PERSPEKTIF THE LOOKING-GLASS SELF - Fitroh Chumairoh (Jurnal Partisipatoris, 2021)
The number of child marriage cases in Indonesia remains high, positioning its rate as the second highest in ASEAN. Child marriage is driven by several dominant factors such as social and cultural pressures. This paper discusses child marriage due to socio-cultural pressures such as out-of-wedlock pregnancy or the local culture of marrying off children early to avoid violating social values and norms. The many negative impacts of child marriage include reproductive health problems, poverty, the risk of domestic violence, divorce, and mentally unprepared parents not taking care of their children properly. The concept of the looking-glass self coined by Charles Horton Cooley was used to analyze this phenomenon since individuals see themselves being related to society. Individuals will perceive themselves based on the results of their interactions with others in society. To prevent child marriage, sex education is required in the school curriculum from early childhood to high school level. Parents should also be informed about how to provide appropriate sex education for their children. In addition, the government needs to increase the minimum age limit for marriage and impose sanctions on officials who marry off children. Parents also need to be selective on the television shows for their children and accompany them as they watch. Television station owners, directors, producers, and art workers are also expected to be more creative in producing programs in order to provide not only entertainment, but also education through their shows.